Dermoscopic patterns of melanoma metastases: interobserver consistency and accuracy for metastasis recognition. (8th July 2013) - Costa, J.; Ortiz‐Ibañez, K.; Salerni, G.; Borges, V.; Carrera, C.; Puig, S.; Malvehy, J.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Dermoscopy helps to identify both benign and malignant lesions. In the literature, several dermoscopic features of cutaneous metastases of malignant melanoma (CMMM) are described. What does this study add? We describe five characteristic dermoscopic patterns – blue naevus‐like, naevus‐like, vascular, angioma‐like and unspecific patterns – to help classify CMMM, obtaining good sensitivity and specificity between different readers.